Wound healing after implant surgery in HIV-positive patients. - Harrison, W; Lewis, C; Lavy, C (2002)
We performed a prospective, blind, controlled study on wound infection after implant surgery involving 41 procedures in patients infected with the human immunodeficiency virus (HIV) and 141 in HIV-negative patients. The patients were staged clinically and the CD4 cell count determined. Wound infection was assessed using the asepsis wound score. A risk category was allocated to account for presurgical contamination. In HIV-positive patients, with no preoperative contamination, the incidence of wound infection (3.5%) was comparable with that of the HIV-negative group (5%; p = 0.396). The CD4 cell count did not affect the incidence of infection (r = 0.16). When there was preoperative contamination, the incidence of infection in HIV-positive patients increased markedly (42%) compared with that in HIV-negative patients (11%; p = 0.084). Our results show that when no contamination has occurred implant surgery may be undertaken safely in HIV-positive patients.